Influence of Milling Process of Roasted Cocoa Beans on Size Distribution Change of Cocoa Cotyledon - Sukrisno Widyotomo; Sri Mulato; Edi Suharyanto (Indonesian Coffee and Cocoa Research Institute, 2007)
One of important steps in secondarycocoa process is deshelling cocoa beans roasted. The aim of deshelling is to enrich cotyledon cocoa surface area which affects to reduce energy and processing time with good quality of the chocolate product. The objective of this research is to study the influence of milling process on physical characteristic change of cocoa beans roasted such as size distribution change, geometrical diameter average, uniformity index, fineness modulus, and average dimension of cotyledoncocoa roasted. The Indonesian Coffee and Cocoa Research Institute has designed and tested deshelling of roasted cocoa beans which will be used in this research. Before deshelling process, C grade bulk cocoa beans has been roasted up to 2.5—3% water contents. The result showed that optimal milling process by rotary cutter type milling unit has good size distribution change, geometrical diameter average, uniformity index, fineness modulus, and average dimension on 500 rpm rotary speed and 2.8 m/s air flow. On optimal process condition, 74.5% of cocoa cotyledon roasted has diameter size between 2.0—4.75 mm, 2.116 mm average of geometrical diameter, 0.864 mm average dimension, 3.052 fineness modulus, and 80% as crude size particel-20% as temperate size particel on uniformity index. Therefore, more than 80% of cocoa cotyledon roasted has diameter size between 2.0—4.75 mm with 700—900 rpm rotary cutter speed. Average of geometric diameter was 1.65—2.19 mm, and the dimension average was 0.69—0.89 mm. Uniformity index was crude size particle up to 80—90%, and in temperate size particle10—20%. Fineness modulus value was 2.73—3.09. Key words: cocoa, milling, size distribution, roasted beans.